PARADIGMS THAT SHAPE STUDENT CREATIVITY REVIEWED FROM THE CHARACTERISTICS OF THE INDEPENDENT CURRICULUM - Irwan; Ilham Akbar; Zuhri (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to determine the paradigm that can shape the creativity of students, assist educators in developing creativity in students and prepare creative educational units based on the characteristics of an independent curriculum. The method used in this study is descriptive qualitative by looking at literature reviews from various sources that have been obtained and then conclusions are drawn analytically. The results of the research are in the form of descriptions of actions that can shape the creativity of students, as well as attitudes of educators that can support learning achievement in implementing the independent curriculum in learning in educational units.